2020
DOI: 10.1038/s41398-020-0784-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of lithium treatment associated effects on brain structure and peripheral gene expression reveals novel molecular insights into mechanism of action

Abstract: Lithium is a highly effective medication for bipolar disorder, but its mechanism of action remains unknown. In this study, brain MRI scans and blood samples for gene expression (total of 110 scans and 109 blood samples) were collected from 21 bipolar subjects before and after 2 and 8 weeks of lithium monotherapy and at the same timepoints from untreated 16 healthy controls. We used linear mixed-effects models to identify brain structural features and genes with expression changed after lithium treatment, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Lithium appears to modulate genes involved in neuroprotection, neuronal plasticity and other neuronal functions including neurotrophy (Malhi et al, 2012). This was further shown in a recent study where magnetic resonance imaging (MRI) scans showed increased grey matter, putamen, hippocampal and thalamic volumes in patients taking lithium as a consequence of lithium-induced gene expression (Anand et al, 2020). Further neuroprotection is evidenced as lithium prevents stress-induced dendritic damage (Wood et al, 2004) and shows anti-apoptotic activity (Bachmann et al, 2009; Chen and Chuang, 1999).…”
Section: Discussionmentioning
confidence: 64%
“…Lithium appears to modulate genes involved in neuroprotection, neuronal plasticity and other neuronal functions including neurotrophy (Malhi et al, 2012). This was further shown in a recent study where magnetic resonance imaging (MRI) scans showed increased grey matter, putamen, hippocampal and thalamic volumes in patients taking lithium as a consequence of lithium-induced gene expression (Anand et al, 2020). Further neuroprotection is evidenced as lithium prevents stress-induced dendritic damage (Wood et al, 2004) and shows anti-apoptotic activity (Bachmann et al, 2009; Chen and Chuang, 1999).…”
Section: Discussionmentioning
confidence: 64%
“…Prolonged stress causes atrophy of brain structures, loss of glial cells, and extensive shrinkage of the apical dendritic tree, hampering adaptive plasticity and compromising resilience. Of note, administration of serotonin reuptake inhibitors increases hippocampus volume (Maller et al, 2018), whereas lithium treatment increases the volume of gray matter (Anand et al, 2020). Mechanistically, transcription factors, epigenetic modulators, and chaperones are fundamental mediators of the adaptive responses in brain circuits.…”
Section: Llmentioning
confidence: 99%
“…7 Despite its widespread use for more than 60 years as a treatment for bipolar disorder, lithium's mode of action needs to be better understood, as does the reason why it is effective in only about 30% of people with bipolar disorder. 11,12 Studies aimed at elucidating lithium's mode of action have found macroscopic changes in brain structure 13 and alterations at the cellular level. 14 For the latter, acute lithium administration has been shown to increase glutamate signalling.…”
Section: Introductionmentioning
confidence: 99%